Computation of stress intensity factor for multiple cracks using singular finite element - Ruslizam, Daud; Ahmad Kamal, Ariffin; Shahrum, Abdullah; A. Emran, Ismail; A., Zulkifli (Trans Tech Publications, 2011)
Link to publisher's homepage at http://www.scientific.net/